(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Indian Literature in English has traveled far to accomplish its present glory and grandeur. At present various ladies essayists through their works offer penetrative knowledge into the mind boggling issues of life. The fictional worries of these ladies scholars break down the universe of ladies, their sufferings as casualties of male authority they likewise express social, monetary and political changes in Indian culture. Among these ladies journalists Shobha De and Nayantara Sahgal has earned a different space for their specific consideration towards mental knowledge and existential concerns. These new age of authors discussed the self-acknowledgment of ladies. The high class, taught, reasonable ladies moved toward becoming hero in t beneficiary books. Their ladies were new class of ladies whose lives were not swarmed by issues of dowry or poverty. These Indian ladies carried on with a favored life to the extent material measures are concerned, however there was something needing, some vacuum in their lives. These ladies were confronting the issue of personality. They show worry about fundamental human issues and to them lady is a mother, a spouse, a little girl, a housewife, a working lady or more all she is a lady. Their ladies are the casualties of a male-overwhelmed society. In their books men are not generally delinquents or oppressors. They investigate the character of the oppressor and demonstrate an all-encompassing way to deal with the issues of ladies through their books. They have raised lady’s issues and endeavored to reach to their answers also. An endeavor has been made through this paper about the status of Indian ladies in the compositions of Shobha De and Nayantara Sahgal in which they speak to new profound quality, as indicated by which lady isn’t to be taken as a simple toy, an object of lust and flitting delight, yet man’s equivalent and regarded accomplice. Their ladies characters without a doubt uncover their feminist ideology. The paper tries to give a similar investigation of the picture of lady in the books of Shobha De and Nayantara Sahgal.